Neoliberalism versus Neolaborism: Dystopia versus Utopia and the future of civilization - Copertari, Luis F. (Advances in Social Sciences Research Journal, 2018)
The ideas of neoliberalism and neolaborism are illustrated using very simple and clear models of reality. What used to work about thirty years ago is no longer valid. Technological incorporation into the economy is forcing us to propose a novel way in which the economies of the world should be managed. The excesses of neoliberalism are leading to a troubling dystopia. Neolaborism, on the other hand, is a new way to approach socioeconomic and political reality, with very practical recommendations and a utopian view of the future of human civilization.